High-temperature-resistant polyimide diaphragm and preparation method thereof

By introducing a uniform mesoporous structure and high-temperature carbonization treatment into the polyimide battery separator, the problem of large pore size and uneven distribution in the prior art is solved, and uniform deposition of lithium ions and lithium dendrites are achieved, which improves the safety and heat resistance of the battery.

CN119560727APending Publication Date: 2025-03-04HUANGGANG NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411762746.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The pore size of the polyimide battery prepared in the prior art is large and unevenly distributed, which can easily lead to lithium dendrites piercing the diaphragm, causing battery short circuits, and pose safety hazards.

Method used

A uniform mesoporous structure is introduced into the polyimide separator by a gentle block polymer template method, and a phenolic resin precursor is used as a crosslinking agent to control the microscopic phase separation structure and heat treatment process to form a polyimide separator with a good pore structure, and enhance mechanical strength and heat resistance through high-temperature carbonization.

Benefits of technology

It realizes uniform deposition of lithium ions, inhibits the growth of lithium dendrites, improves the safety and service life of the battery, and maintains the existence of the pore structure under high temperature conditions, enhancing the heat resistance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560727A_ABST
    Figure CN119560727A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymeric membrane materials, and particularly relates to a high-temperature-resistant polyimide membrane and a preparation method thereof.The preparation method comprises the steps that 1, aromatic diamine and aromatic dianhydride are subjected to condensation polymerization, and ether-containing polyamide acid is obtained; (2) preparing an amphiphilic block polymer of which the molecular weight distribution is not greater than 1.15 by using an anionic polymerization method or a free radical polymerization method; (3) mixing ether-containing polyamide acid, the amphiphilic block polymer and a phenolic resin cross-linking agent, adding the mixture into a polar aprotic solvent, and stirring to obtain a precursor solution; and (4) casting the precursor solution, heating and crosslinking to obtain the polyimide diaphragm. The thickness of the prepared diaphragm is 50-200 microns, the diaphragm can resist high temperature up to 900 DEG C, the safety performance of the battery in a high-temperature environment can be effectively improved, the uniform mesoporous structure of the diaphragm is beneficial to guiding uniform deposition of lithium ions and fundamentally inhibiting growth of lithium dendrites, and the good flexibility and mechanical property can meet the normal use requirement of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a high-temperature resistant polyimide diaphragm and a carbonized film, and belongs to the technical field of polymer film materials. Background Art

[0002] The diaphragm is an important component of lithium-ion batteries. The current commercial polyolefin diaphragms have poor heat resistance (PE has a melting point of only 136°C). When the battery temperature exceeds 160°C, it will melt and cause a serious internal short circuit, which can easily cause the battery to catch fire or explode, thus posing a safety hazard. Solving the battery safety problem is urgent.

[0003] The polyimide separator with a rigid aromatic ring and imide ring structure has good heat resistance and can withstand thermal failure caused by battery overcharging. The presence of its lone pair of electrons in the ether bond can also react with Li + Interaction promotes Li + transmission, becoming a very promising polyolefin replacement material. At present, the preparation methods of polyimide battery separators include electrostatic spinning, phase conversion, inorganic filler method, etc. For example, document 1CN109524598A, document 2CN113718536A, etc. use electrostatic spinning to prepare polyimide fiber separators with high porosity and high temperature resistance, but the PI fiber membrane prepared by electrostatic spinning produces interconnected and wide pores, which are more likely to form lithium dendrites, and lithium dendrites are prone to pierce the separator, causing battery short circuit; for example, the polyimide prepared by the phase conversion method of patent CN101645497A has high production efficiency, but it often has the problem of uneven pore size distribution, which cannot meet the use requirements of lithium batteries; document 3CN114883740A, document 4CN108172740A not only add inorganic fillers and pore-forming agents, but also require the addition of subsequent processing equipment, and the prepared separator has a large pore size and uneven distribution. Reference 5 "Nanomaterials.2020(10)1-15; J.Electrochem.Soc.2019(166)A754–761" reported that a PI membrane with a three-dimensional ordered macroporous (3DOM) structure with a pore size greater than 300nm controls the current distribution through precise pore control, promotes the uniform deposition of lithium ions and effectively reduces the formation of lithium dendrites. The results show that the smaller the pore size of the 3DOM PI membrane, the higher the cycling performance of the lithium metal negative electrode. Reference 6 "Adv.Sci.2021(8)2003096" reported that a BCP membrane with a pore size of 30nm was formed by a selective swelling method, showing an electrolyte absorption rate of 500% and a 10mS cm -1 It has high ionic conductivity, but needs to be improved in terms of heat resistance and porosity. Summary of the invention

[0004] In order to overcome the problem that the pore size of the polyimide battery separator prepared by the prior art is large and unevenly distributed, and lithium dendrites are prone to piercing the separator, and to improve battery safety and extend the service life of the battery, the present invention provides a high temperature resistant polyimide battery separator and a preparation method thereof, which aims to introduce a uniform mesoporous structure into the polyimide separator by a mild block polymer template method to fundamentally dredge the lithium ion transport channel and inhibit the growth of interfacial lithium dendrites. The present invention does not require an extra pore former removal step, and the block polymer and the cross-linking agent can be carbonized at high temperature to contribute to the mechanical strength and heat resistance of the carbonized film. The uniform mesopores that still exist after carbonization can solve the safety problem of lithium batteries in the prior art while optimizing battery performance.

[0005] According to a first aspect of the present invention, the present invention first provides a method for preparing a high temperature resistant polyimide membrane, comprising the following steps:

[0006] (1) stirring an aromatic diamine and an aromatic dianhydride to carry out a polycondensation reaction, and obtaining an ether-containing polyamic acid after precipitation and drying;

[0007] (2) preparing an amphiphilic block polymer by anionic polymerization or free radical polymerization, so that the molecular weight distribution of the amphiphilic block polymer is no more than 1.15, and the amphiphilic block polymer comprises an etchable hydrophobic block and a cross-linkable hydrophilic block;

[0008] (3) mixing the ether-containing polyamic acid obtained in step (1), the amphiphilic block polymer obtained in step (2) and the phenolic resin crosslinking agent into a polar aprotic solvent, and stirring to obtain a precursor solution;

[0009] (4) Casting the precursor solution and heating it for cross-linking to obtain a polyimide membrane.

[0010] According to one embodiment of the present invention, the molar ratio of the aromatic diamine to the aromatic dianhydride in step (1) is 1:1; wherein the aromatic diamine is one or more of 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-diaminodiphenyl ether, 1,3,5-tri(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene; and the aromatic dianhydride is one or more of pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, and 4,4'-phenylenedioxydiphthalic anhydride.

[0011] According to one embodiment of the present invention, the etchable hydrophobic block in step (2) is at least one of polystyrene, polymethylstyrene, polyisoprene, and poly(2-vinylpyridine); the cross-linkable hydrophilic block is at least one of poly(methacrylic acid), poly(4-vinylphenol), polyethylene oxide, poly(glycidyl methacrylate), and oligomeric silsesquioxane; and the block ratio of the two blocks of the block polymer is (0.6 to 0.4): (0.4 to 0.6).

[0012] According to one embodiment of the present invention, in step (3), the mass ratio of the polyamic acid: block polymer: phenolic resin precursor is (0.3-0.5): (0.3-0.65): (0.05-0.2); the aprotic solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran.

[0013] According to one embodiment of the present invention, the casting in step (4) is to scrape the precursor solution onto the substrate at 20-25°C and slowly cast it; the heating crosslinking treatment process is: first, keep the temperature at 70-100°C for 1.5 hours to remove the solvent, then raise the temperature to 160-180°C to complete the thermal micro-crosslinking process of the crosslinking agent phenolic resin precursor and the thermal decomposition pore-forming process of the block polymer, and keep the temperature for 2 hours; finally, raise the temperature to 280-350°C for thermal imidization process, and keep the temperature for 1 hour.

[0014] According to one embodiment of the present invention, the method further comprises the step (5): calcining the polyimide membrane obtained in the step (4) at 500-900° C. to obtain a carbonized polyimide membrane.

[0015] According to one embodiment of the present invention, the preparation process of the carbonized film in step (5) is as follows: the polyimide membrane obtained in step (4) is heated to 500° C., kept at this temperature for 2 hours, and then heated to 900° C., and kept at this temperature for 2 hours.

[0016] According to another aspect of the present invention, the present invention also provides an ultra-thin polyimide membrane obtained by the above preparation method, wherein the thickness of the polyimide membrane is 50 to 200 μm.

[0017] According to another aspect of the present invention, the present invention also provides the use of the ultra-thin polyimide separator in a lithium battery.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The phenolic resin precursor added in the method of the present invention is a cross-linking agent that reacts slowly at low temperatures, which is beneficial to controlling the regular microscopic phase separation structure that has been formed. Once the microstructure is fixed by the cross-linking structure, the degree of damage to the structure caused by further heating is greatly reduced, which is also beneficial to the subsequent pore formation and thermal imidization to form a polyimide membrane.

[0020] (2) The method of the present invention is mild and pollution-free, environmentally friendly, and the formed pore structure is uniform and small in diameter, which is conducive to the uniform deposition of lithium ions and inhibits the growth of lithium dendrites. It can be applied to lithium batteries with high safety and long life.

[0021] (3) The polyimide separator prepared by the present invention contains a rigid aromatic ring structure and a flexible ether bond, has good flexibility and interface compatibility, and is conducive to the assembly of practical lithium batteries;

[0022] (4) The polyimide separator of the present invention can withstand a high temperature of 900°C and maintain the pore structure, further improving the safety of the battery at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the small-angle X-ray diffraction pattern of the polyimide membrane prepared in Example 1 after heat treatment at 350°C.

[0024] Figure 2 This is a scanning electron microscope image of the polyimide membrane prepared in Example 1.

[0025] Figure 3 This is a scanning electron microscope image of the polyimide membrane prepared in Example 2.

[0026] Figure 4 This is a scanning electron microscope image of the polyimide membrane prepared in Example 3.

[0027] Figure 5 This is a scanning electron microscope image of the polyimide membrane prepared in Example 1 after heat treatment at 900°C.

[0028] Figure 6 This is a scanning electron microscope image of the polyimide membrane prepared in Example 1 after heat treatment at 900°C. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] The present invention first provides a method for preparing a high temperature resistant polyimide diaphragm, comprising:

[0031] (1) stirring an aromatic diamine and an aromatic dianhydride to carry out a polycondensation reaction, and obtaining an ether-containing polyamic acid after precipitation and drying;

[0032] (2) preparing an amphiphilic block polymer by anionic polymerization or free radical polymerization, so that the molecular weight distribution of the amphiphilic block polymer is no more than 1.15, and the amphiphilic block polymer comprises an etchable hydrophobic block and a cross-linkable hydrophilic block;

[0033] (3) mixing the ether-containing polyamic acid obtained in step (1), the amphiphilic block polymer obtained in step (2) and the phenolic resin crosslinking agent into a polar aprotic solvent, and stirring to obtain a precursor solution;

[0034] (4) Casting the precursor solution and heating it for cross-linking to obtain a polyimide membrane.

[0035] The key point of the method of the present invention lies in the influence and control of heat treatment on the mesoporous structure, wherein the formation and control mechanism of the mesoporous structure is: 1. The hydrophilic end block polymer and the polyamic acid are combined with hydrogen bonding forces to form a hydrophilic phase, and then self-assemble with the hydrophobic phase to form a regular microscopic phase separation structure; 2. The collapse of the microscopic phase separation structure during the heat treatment process is controlled by low-temperature curing of the cross-linking agent, and the slow heat treatment reduces the influence of block polymer etching and thermal imidization on the mesoporous structure.

[0036] The following are specific embodiments:

[0037] Example 1

[0038] A method for preparing a high temperature resistant polyimide diaphragm is prepared by the following preparation steps:

[0039] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3 to 4 hours to obtain a precursor solution with a viscosity of 0.4 to 0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;

[0040] 2) Polymethylstyrene (PαMS) and poly(methyl methacrylic acid) (PtBMA) with a protective group are polymerized by anionic polymerization to obtain BCP-1 (PαMS-b-PMAA, 60:40 wt%) having a number average molecular weight of 50,000 to 60,000 and a molecular weight distribution (PDI) of 1.15;

[0041] 3) 0.04 g of precursor powder, 0.04 g of BCP-1 and 0.02 g of crosslinking agent phenolic resin precursor were dissolved in 10 ml of N, N-dimethylacetamide and stirred at room temperature to obtain a uniform precursor solution;

[0042] 4) Pour the above mixed solution on a clean glass plate, scrape and cast to obtain a smooth cast film, then place the glass plate in an oven at 80°C and keep it warm for 1.5 hours, then heat it to 160°C and keep it warm for 2 hours, and finally heat it to 350°C and keep it warm for 1 hour. The SAXS and SEM images of the obtained high temperature resistant polyimide membrane are shown in Figure 1 and Figure 2 As shown, the existence of uniform mesoporous structure is proved. The thickness of the high temperature resistant polyimide separator obtained in this embodiment is 50 μm.

[0043] 5) The polyimide membrane obtained in step (4) was placed in a heater at 500°C for 2 hours, then heated to 900°C for 2 hours to obtain a carbonized polyimide membrane. The scanning electron microscope image is as follows: Figure 5 and Figure 6 As shown, it can be seen that the uniform mesoporous structure still exists, and the pore size is slightly increased.

[0044] Example 2

[0045] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3 to 4 hours to obtain a precursor solution with a viscosity of 0.4 to 0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain an ether-containing polyamic acid;

[0046] 2) Polymethylstyrene (PαMS) and poly (2-vinylpyridine) (P2VP) are polymerized by anionic polymerization to obtain BCP-2 (PαMS-b-P2VP, 60:40 wt%) having a number average molecular weight of 50,000 to 60,000 and a molecular weight distribution (PDI) of 1.1;

[0047] 3) 0.04 g of precursor powder, 0.04 g of BCP-2 and 0.02 g of crosslinking agent phenolic resin precursor were dissolved in 10 ml of N, N-dimethylacetamide and stirred at room temperature to obtain a uniform mixed solution;

[0048] 4) Pour the above mixed solution onto a clean glass plate, scrape and cast to obtain a smooth cast film, then place the glass plate in an oven at 80°C, keep warm for 1.5 hours, then heat to 160°C, keep warm for 2 hours, and finally heat to 350°C and keep warm for 1 hour.

[0049] 5) The polyimide membrane obtained in step (4) was placed in a heater at 500°C for 2 hours, then heated to 900°C for 2 hours to obtain a carbonized polyimide membrane. Figure 3 As shown, the existence of a uniform mesoporous structure is proved. The thickness of the high temperature resistant polyimide separator obtained in this embodiment is 115 μm.

[0050] Example 3

[0051] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-dioxyphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3 to 4 hours to obtain a precursor solution with a viscosity of 0.4 to 0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;

[0052] 2) Polymethylstyrene (PαMS) and poly(methyl methacrylic acid) (PtBMA) with a protective group are polymerized by anionic polymerization to obtain BCP-1 (PαMS-b-PMAA, 60:40 wt%) having a number average molecular weight of 50,000 to 60,000 and a molecular weight distribution (PDI) of less than 1.1;

[0053] 3) 0.04 g of precursor powder, 0.04 g of BCP-1 and 0.02 g of crosslinking agent phenolic resin precursor were dissolved in 10 ml of N, N-dimethylacetamide and stirred at room temperature to obtain a uniform precursor solution;

[0054] 4) Pour the above precursor solution onto a clean glass plate, then place the glass plate in an oven at 80°C for 1.5 hours, then heat it up to 160°C for 2 hours, and finally heat it up to 350°C for 1 hour. Use a scraper to scrape the film to obtain a smooth polyimide membrane, as shown in the SEM image. Figure 4 As shown, the existence of a uniform mesoporous structure is proved. The thickness of the polyimide battery separator is 76 μm.

[0055] 5) placing the polyimide membrane obtained in step (4) in a heater at 500° C., keeping the temperature for 2 h, then raising the temperature to 900° C., keeping the temperature for 2 h, to obtain a carbonized polyimide membrane.

[0056] Comparative Example 1

[0057] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3 to 4 hours to obtain a precursor solution with a viscosity of 0.4 to 0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;

[0058] 2) Polymethylstyrene (PαMS) and poly(methacrylic acid) (PtBMA) with a protective group are polymerized according to the anionic polymerization method of the present invention to obtain BCP-3 (PαMS-b-PMAA, 60:40 wt%) having a number average molecular weight of 30,000 to 40,000 and a molecular weight distribution PDI of 1.3;

[0059] 3) 0.04 g of precursor powder, 0.04 g of BCP-3 and 0.02 g of crosslinking agent phenolic resin precursor were dissolved in 10 ml of N, N-dimethylacetamide and stirred at room temperature to obtain a uniform precursor solution;

[0060] 4) Pour the above mixed solution onto a clean glass plate, scrape and cast to obtain a smooth cast film, then place the glass plate in an oven at 80°C, keep warm for 1.5 hours, then heat to 160°C, keep warm for 2 hours, and finally heat to 350°C and keep warm for 1 hour.

[0061] Comparative Example 2

[0062] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3 to 4 hours to obtain a precursor solution with a viscosity of 0.4 to 0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;

[0063] 2) Polymethylstyrene (PαMS) and poly(methacrylic acid) (PtBMA) with a protective group are polymerized according to the anionic polymerization method of the present invention to obtain BCP-4 (PαMS-b-PMAA, 80:20wt%) with a number average molecular weight of 50,000 to 60,000 and a molecular weight distribution PDI of 1.15;

[0064] 3) 0.04 g of precursor powder, 0.04 g of BCP-4 and 0.02 g of crosslinking agent phenolic resin precursor were dissolved in 10 ml of N, N-dimethylacetamide and stirred at room temperature to obtain a uniform precursor solution;

[0065] 5) Pour the above mixed solution onto a clean glass plate, scrape and cast to obtain a smooth cast film, then place the glass plate in an oven at 80°C, keep warm for 1.5 hours, then heat to 160°C, keep warm for 2 hours, and finally heat to 350°C and keep warm for 1 hour.

[0066] Comparative Example 3

[0067] 1) dissolving 1,4-bis(4-aminophenoxy)benzene and 4,4'-oxydiphthalic anhydride in N,N-dimethylacetamide at a ratio of 1:1 mol and reacting in an ice bath for 3 to 4 hours to obtain a precursor solution with a viscosity of 0.4 to 0.5 dL / g, precipitating with water, filtering and vacuum drying to obtain a flexible ether-containing polyamic acid;

[0068] 2) Polymethylstyrene (PαMS) and poly(methacrylic acid) (PtBMA) with a protective group are polymerized according to the anionic polymerization method of the present invention to obtain BCP-1 (PαMS-b-PMAA, 60:40wt%) with a number average molecular weight of 50,000 to 60,000 and a molecular weight distribution PDI of 1.15;

[0069] 3) 0.058 g of precursor powder, 0.04 g of BCP-1 and 0.002 g of crosslinking agent phenolic resin precursor were dissolved in 10 ml of N, N-dimethylacetamide and stirred at room temperature to obtain a uniform precursor solution;

[0070] 4) Pour the above mixed solution onto a clean glass plate, scrape and cast to obtain a smooth cast film, then place the glass plate in an oven at 80°C, keep warm for 1.5 hours, then heat to 160°C, keep warm for 2 hours, and finally heat to 350°C and keep warm for 1 hour.

[0071] The performance of the battery separators obtained in Examples 1-3 and Comparative Examples 1-3 was characterized, see Table 1.

[0072] Table 1: Performance comparison of battery separators obtained in Examples 1-3 and Comparative Examples 1-3

[0073]

[0074] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high temperature resistant polyimide diaphragm, characterized in that: The following steps are involved: (1) stirring an aromatic diamine and an aromatic dianhydride to carry out a polycondensation reaction, and obtaining an ether-containing polyamic acid after precipitation and drying; (2) preparing an amphiphilic block polymer by anionic polymerization or free radical polymerization, so that the molecular weight distribution of the amphiphilic block polymer is no more than 1.15, and the amphiphilic block polymer comprises an etchable hydrophobic block and a cross-linkable hydrophilic block; (3) mixing the ether-containing polyamic acid obtained in step (1), the amphiphilic block polymer obtained in step (2) and the phenolic resin crosslinking agent into a polar aprotic solvent, and stirring to obtain a precursor solution; (4) Casting the precursor solution and heating it for cross-linking to obtain a polyimide membrane.

2. The method for preparing a high temperature resistant polyimide diaphragm according to claim 1, characterized in that: The molar ratio of the aromatic diamine to the aromatic dianhydride in step (1) is 1:1; wherein the aromatic diamine is one or more of 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-diaminodiphenyl ether, 1,3,5-tri(4-aminophenoxy)benzene, and 1,4-bis(4-aminophenoxy)benzene; and the aromatic dianhydride is one or more of pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, and 4,4'-phenylenedioxydiphthalic anhydride.

3. The method for producing a high temperature resistant polyimide membrane according to claim 1, characterized in that: The etchable hydrophobic block in step (2) is at least one of polystyrene, polymethylstyrene, polyisoprene, and poly(2-vinylpyridine); the cross-linkable hydrophilic block is at least one of poly(methacrylic acid), poly(4-vinylphenol), polyethylene oxide, poly(glycidyl methacrylate), and oligomeric silsesquioxane; and the block ratio of the two blocks of the block polymer is (0.6-0.4):(0.4-0.6).

4. The method for producing a high temperature resistant polyimide membrane according to claim 1, characterized in that: In step (3), the mass ratio of polyamic acid: block polymer: phenolic resin precursor is (0.3-0.5): (0.3-0.65): (0.05-0.2); the aprotic solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone and tetrahydrofuran.

5. The method for producing a high temperature resistant polyimide membrane according to claim 1, characterized in that: The casting in step (4) is to scrape the precursor solution onto the substrate at 20-25°C and slowly cast it; the heating crosslinking treatment process is: first, keep the temperature at 70-100°C for 1.5 hours to remove the solvent, then heat it to 160-180°C to complete the thermal micro-crosslinking process of the crosslinking agent phenolic resin precursor and the thermal decomposition pore-forming process of the block polymer, and keep it for 2 hours; finally, heat it to 280-350°C for thermal imidization process, and keep the thermal imidization process for 1 hour.

6. The method for producing a high temperature resistant polyimide membrane according to claim 1, characterized in that: The method further comprises step (5): calcining the polyimide membrane obtained in step (4) at 500-900° C. to obtain a carbonized polyimide membrane.

7. The method for producing a high temperature resistant polyimide membrane according to claim 6, characterized in that: The preparation process of the carbonized film in step (5) is as follows: the polyimide membrane obtained in step (4) is heated to 500° C., kept at this temperature for 2 hours, and then heated to 900° C., and kept at this temperature for 2 hours.

8. An ultra-thin polyimide membrane prepared by the method according to any one of claims 1 to 7, characterized in that: The thickness of the polyimide membrane is 50-200 μm.

9. Use of the ultra-thin polyimide separator as claimed in claim 8 in a lithium battery.

Citation Information

Patent Citations

  • Polyimide porous membrane, preparation method thereof and lithium ion battery

    CN101645497A

  • Battery diaphragm and preparation method thereof

    CN109524598A